Farming systems and soil fertility management practices in smallholdings on the southern slopes of Mount Kilimanjaro, Tanzania - Mhoro, Lydia; Meya, Akida Ignas; Amuri, Nyambilila Abdallah; Ndakidemi, Patrick Alois; Mtei, Kelvin Marck; Njau, Karoli Nicholas (Frontiers in Agronomy, 2024)
In the northern part of Tanzania, the slopes of Mount (Mt.) Kilimanjaro are the most important areas, both in terms of socio-economic development and ecological succession. The main agricultural systems in the area are banana-based (in the highlands) and maize-based (in the lowlands), with strong interlinkage between them via residual transfer from the lowlands to the mountains. This study assessed the soil fertility status between the two contrasting farming areas of highland and lowland farms along the slopes of Mt. Kilimanjaro. To achieve this, smallholder farmers along the slope [from above 1000 meters above sea level (m.a.s.l) banana-based down to maize-based, i.e., less than 1000 m.a.s.l] who practice crop residual transfer from maize-based to banana-based farming systems were selected. Qualitative information regarding the demographics, farming practices, and soil fertility management in the two areas were gathered using a semi-structured questionnaire. Soils from both areas (highland and lowland farms) were collected and analyzed in the laboratory for the key soil properties. The demographic results show that agriculture is mostly done by adults and elders (>40 years old). Manure was most commonly reported to be used in the highlands, while inorganic fertilizers were mainly used in lowland areas. The major challenges for soil fertility management are a shortage of manure and high cost of inorganic fertilizers. The results of soil nutrients revealed that lowland zones (>1000 m.a.s.l.) had significantly (p< 0.01) lower levels of nitrogen (0.14%) and organic carbon (OC) (1.22%) compared with highland zones. Extractable phosphorus (P) was significantly lower in both the highland and lowland zones, at 9.3 mg kg -1 and 8.2 mg kg -1 , respectively, compared with other nutrients. However, potassium (K + ) was significantly (p<0.01) lower [0.34 cCmol (+) kg -1 ] in the highland zone compared to lowland areas. The data show that there is a severe depletion of soil nutrients in the lowland area of Hai district. Notwithstanding the efforts of the small-holder farmers; the study comes to the conclusion that increasing agricultural yield and the sustainability of farming systems require replenishing the nutrients in the soil along the slope of Mount Kilimanjaro